Mining DNA methylation alterations towards a classification of placental pathologies. (30th October 2017) - Wilson, Samantha L; Leavey, Katherine; Cox, Brian J; Robinson, Wendy P
Abstract: Placental health is a key component to a successful pregnancy. Placental insufficiency (PI), inadequate nutrient delivery to the fetus, is associated with preeclampsia (PE), a maternal hypertensive disorder, and intrauterine growth restriction (IUGR), pathologically poor fetal growth. PI is more common in early-onset PE (EOPE) than late-onset PE (LOPE). However, the relationship between these disorders remains unclear. While DNA methylation (DNAm) alterations have been identified in PE and IUGR, these entities can overlap and few studies have analysed them separately. This study aims to utilize DNAm profiling to better understand the underlying placental variation associated with PE and IUGR. Placental samples from a discovery (43 controls, 22 EOPE, 18 LOPE, 11 IUGR) and validation cohort (15 controls, 22 EOPE, 11 LOPE) were evaluated using the Illumina HumanMethylation450 array. To account for gestational age (GA) effects, EOPE samples were compared with pre-term births of varying etiologies (GA <37 weeks). LOPE and IUGR were compared with term controls (GA >37 weeks). While 1703 sites were differentially methylated (DM) (FDR < 0.05, Δβ > 0.1) in EOPE, few changes were associated with LOPE ( N =  5), or IUGR ( N =  0). Of the 1703 EOPE sites, 599 validated in the second cohort. Using these 599 sites, both cohorts clustered into three distinct groups. Interestingly, LOPE samples diagnosed between 34 and 36 weeks with co-occurring IUGR clustered with the EOPE. DNAm profiling may provide an independent tool to refine clinical/pathological diagnoses into subgroups with more uniform pathology. Despite large changes observed in EOPE, there were challenges in reproducing genome-wide DNAm hits that are discussed.